SURGICAL RESECTION OF MACROPROLACTINOMA RESISTANT TO DOPAMINE AGONIST: CASE REPORT - Silva de Lira, Isadora (2022)
Introduction: Prolactin-secreting pituitary tumors comprise about 50% of all pituitary adenomas, of which only 10% are macroadenomas. Case report: Female patient, 63 years old, refers to a decrease in visual acuity for approximately 06 months and headache sporadically. He was evaluated by endocrinology due to hyperprolactinemia, being subjected to an image exam that detected the presence of expansive formation occupying pituitary tissue suggestive of pituitary adenoma. He was then treated with the use of oral cabergoline, without controlling hyperprolactinemia. Control magnetic resonance imaging six months ago showed an increase in the dimensions of the adenoma, and one patient underwent surgical treatment for resection of the pituitary tumor, via transnasal-transfenoidal approach. Comments: Macroprolactinomas are prolactin-secreting tumors, the first clinical treatment of choice, with dopaminergic agonists. Treatment of surgical resection is rare and indicated for cases that do not respond to clinical treatment.